Isolation, phylogenetic analysis and bioprospection of myxobacteria from Vietnam - YEN NGUYEN THI NGOC; CHUNG DUONG DINH; HONG NGUYEN THI KIM; CHAM NGUYEN PHUONG; NHAN VO THI; LINH DINH THI LAN; NGOC NGUYEN LE BAO; THAI NGUYEN MINH; NGA NGUYEN DINH; ANH NGUYEN TU (Society for Indonesian Biodiversity, 2023)
Abstract. Yen NTN, Chung DD, Hong NTK, Cham NP, Nhan VT, Linh DTL, Ngoc NLB, Thai NM, Nga ND, Anh NT. 2023. Isolation, phylogenetic analysis and bioprospection of myxobacteria from Vietnam. Biodiversitas 24: 5653-5663. Myxobacteria have been considered microbial factories for producing secondary metabolites that have a variety of potential biological actions for discovering and isolating new biological molecules. Myxobacteria were isolated from soil samples collected in some provinces/cities in Vietnam. The purified isolates were identified based on morphology, biochemical test and phylogenetic analysis inferred from 16S rRNA gene. High-throughput screening assays including 2,2-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DDPH) for antioxidant properties and microdilution for antimicrobial activity were performed with myxobacterial extracts. Compounds from potential strain were predicted using liquid chromatography coupled with mass spectrometry. Forty-three myxobacterial strains were isolated and classified into seven genera of Angiococcus, Archangium, Chondromyces, Corallococcus, Cystobacter, Melittangium, and Myxococcus. The extract from CT21 strain had the highest total antioxidant activity (IC50 = 52.34 ± 1.47 and 30.28 ± 0.74 ?g/mL for the DPPH and ABTS, respectively). It is worth noting that all strains isolated myxobacterial strains show inhibitory activity against at least one of the tested microorganisms. The most potent antimicrobial strain was Myxococcus stipitatus GL41, which inhibited all tested microorganisms, and the minimal inhibitory concentration (MIC) values were 1 ?g/mL against methicillin-resistant Staphylococcus aureus (MRSA), methicillin-sensitive Staphylococcus aureus (MSSA), Streptococcus faecalis, Candida albicans, and Aspergillus niger. Mass spectrometry analysis revealed the presence of althiomycin - the polyketide antibiotic from ethyl acetate fraction. In the present study, myxobacteria were isolated from soil sample collected from Vietnam, analyzed phylogenetically, and screened for biological activities.